Impacts of STEM Professional Development on Teachers' Knowledge, Self-Efficacy, and Practice - Gardner, Kimberly; Glassmeyer, David; Worthy, Roneisha (Frontiers in Education, 2019)
Research frameworks outline key aspects of STEM (science, technology, engineering, mathematics) integration for teachers, but translating this research into productive changes in teachers' classroom practices remains a challenge, particularly in schools without an emphasis on STEM integration. In this article, we detail how a STEM education descriptive framework was used to design and enact a year-long professional development with eight middle and secondary teachers at non-STEM focused schools in Southeast USA. We examined the professional development impact on teacher content knowledge, self-efficacy, and practice using pre- and post-test scores on a content exam, pre- and post-test scores on a self-efficacy instrument, and self-reported STEM integration efforts. We found teachers improved in their self-efficacy and made productive changes in their classroom practices, though no significant gains in content knowledge was detected. We conclude with how this STEM education descriptive framework can be helpful in designing effective professional development for teachers at non-STEM focused schools.